Metáforas conceptuais que categorizam a reforma trabalhista no gênero charge: uma análise semântico-cognitiva - Andrade, Luiz Henrique Santos de (2019)
This doctoral thesis presents the results of the investigation of how the Labor Reform was conceptualized/categorized in the cartoon genre, through the conceptual metaphors which were used in the construction of this concept. Our objective was to identify, describe and analyze the conceptual metaphors and their linguistic expressions combined with the visual elements used in the corpus. Our central hypothesis was that, from the survey of conceptual metaphors, we would reach in the conceptualization of the Labor Reform and the agents involved in it by the State (Executive, Legislative, most Brazilian entrepreneurs and workers) in the perspective of cartoonists, revealing us some ideological values that underpinned the cartoons. It is important to note that this research is linked to the umbrella project entitled – Metaphors, Discursive Genres and Argumentation (MDGA) –, under the coordination of Professor Dra. Lucienne Espíndola. In regarding to the theoretical assumptions, we used the Theory of Idealized Cognitive Models (ICMs), by Lakoff (1987), the Theory of Conceptual Metaphor, according to Lakoff and Johnson (2002 [1980], 2003), the Metaphorical System of Morality, according to Lakoff and Johnson (1999), Lakoff (1995, 2016 [1996]), and the interface among conceptual metaphor, culture and ideology, according to the studies developed by Kövecses (2000, 2005), Charteris-Black (2004, 2005) and Goatly (2007). The corpus of our work consists of 42 cartoons which were collected in two specialized sites: Online Charge and Political Humor. Furthermore, we used personal blogs of some renowned cartoonists to gather texts on the Labor Reform. It is important to point out that, as categories of analysis, we depart from the conceptual metaphors MORALITY IS WELL-BEING and NATION IS FAMILY and we carried out a descriptive-interpretative analysis of the cartoons. Through the metaphorical ICM, we verified that State representatives (former President Temer and parliamentarians) along with Brazilian entrepreneurs were conceptualized as immoral agents, while the workers were categorized either as slaves or as things/objects, from the point of view of the cartoon producers. Moreover, it was possible to check up that the reform concept was built metaphorically from different source-domains such as: (i) ENSLAVEMENT; (ii) MASSACRE/TORTURE; (iii) PUNISHMENT/PENALTY; (iv) THEFT; (v) DESTRUCTION/WAR; (vi) DEATH; (vii) TRAP/CHEATING; (viii) CUT; and (ix) BARGAINING.